2013
DOI: 10.1039/c3cp53941e
|View full text |Cite
|
Sign up to set email alerts
|

On the limited performances of sulfone electrolytes towards the LiNi0.4Mn1.6O4 spinel

Abstract: Cycling after storage of LiNi0.4Mn1.6O4/Li4Ti5O12 cells evidences lower total capacity losses for EMS-, TMS- and MIS-based electrolytes as compared to EC-based at 20 °C. The shuttle-type mechanism induced by the electrolyte oxidation is mainly present in the accumulators at this temperature, as compared to those due to the Mn(2+) and Ni(2+) dissolution. At 30 and 40 °C, EC is responsible for the polymer film formation on the LiNi0.4Mn1.6O4 surface, which limits the transition metal ion dissolution. This result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In terms of LiNi 0.5 Mn 1.5 O 4 , changing particle sizes and shapes, , coating, , and element doping ,, are usually adopted. In terms of electrolyte, the reported solutions include search novel high voltage electrolytes, optimization the conventional electrolyte by other additives, and application of ionic liquids. …”
Section: Surface and Interface Chemistrymentioning
confidence: 99%
“…In terms of LiNi 0.5 Mn 1.5 O 4 , changing particle sizes and shapes, , coating, , and element doping ,, are usually adopted. In terms of electrolyte, the reported solutions include search novel high voltage electrolytes, optimization the conventional electrolyte by other additives, and application of ionic liquids. …”
Section: Surface and Interface Chemistrymentioning
confidence: 99%
“…Demeaux et al reported that sulfones are promising solvents for high-voltage cathodes in LIBs, 60 although they cannot prevent the dissolution of Mn 2+ and Ni 2+ in the electrolyte due to the lack of surface films forming on the LNMO cathode. 77 Note that sulfone-based electrolytes must include an SEI former for their successful application in cells with graphite anodes. 65 The Angell group observed that the all sulfone-based electrolyte ethyl methyl sulfone (EMS)/fluoromethyl sulfone (FMS) (see the chemical structure of sulfone-based solvents in Fig.…”
Section: Interfacial Properties Of Limn 2 O 4 1 Surface Chemistry mentioning
confidence: 99%
“…Demeaux et al reported that sulfones are promising solvents for high-voltage cathodes in LIBs, although they cannot prevent the dissolution of Mn 2+ and Ni 2+ in the electrolyte due to the lack of surface lms forming on the LNMO cathode. 77 Note that sulfone-based electrolytes must include an SEI former for their successful application in cells with graphite anodes.…”
Section: Functional Additives For Licoo 2 and Lithium Nickel Cobalt M...mentioning
confidence: 99%
“…In order to achieve reliable battery packs for these applications, various thrusts of research and development must be conducted simultaneously, including but not limited to the design of advanced battery materials, cell configuration, circuit optimization, and diagnostics. With respect to the chemistries of electrode materials, various analytical diagnostic tools have been performed to probe chemical and structural environments from the bulk to the surface56789. In-depth diagnostic analysis can provide insights into structure-property relationships1011 as well as into failure mechanisms1213.…”
mentioning
confidence: 99%